In vivo serum titanium ion levels following modular neck total hip arthroplasty: 10 year results in 67 patients - Omlor, Georg; Kretzer, Jan Philippe; Reinders, Jörn; Streit, Marcus R.; Bruckner, Thomas; Gotterbarm, Tobias; Merle, Christian (Acta biomaterialia, 2013)
The objective of the present cross-sectional study was to determine in vivo titanium ion levels following cementless total hip arthroplasty (THA) using a modular stem system with different shapes for femoral canal fit and multiple neck options. A consecutive series of 173 patients (190 hips) who underwent cementless modular neck THA and a ceramic on polyethylene bearing with a median follow-up of 9 (7-13) years was evaluated retrospectively. According to a standardized protocol, titanium ion measurements were performed on 67 patients using high-resolution inductively coupled plasma-mass spectrometry. Ion levels were compared to a control group comprising patients with non-modular titanium implants (n=11) and to individuals without implants (n=23). Modular neck THA did not result in elevated titanium ion levels compared to non-modular THA. Compared to individuals without implants, both modular THA and non-modular THA showed elevated titanium ion levels. Absolute titanium ion levels, however, were comparatively low for both implants. The data suggest that the present modular stem system does not result in elevated systemic titanium ion levels in the medium term when compared to non-modular stems. Further longitudinal studies are needed to evaluate the use of systemic titanium ion levels as an objective diagnostic tool to identify THA failure and to monitor patients following revision surgery.